Populus homeobox gene ARBORKNOX1 reveals overlapping mechanisms regulating the shoot apical meristem and the vascular cambium - Groover, A.T; Mansfield, S.D; DiFazio, S.P; Dupper, G; Fontana, J.R; Millar, R; Wang, Y (Plant molecular biology, 2006)
Secondary growth is supported by a dividing population of meristematic cells within the vascular cambium whose daughter cells are recruited to differentiate within secondary phloem and xylem tissues. We cloned a Populus Class 1 KNOX homeobox gene, ARBORKNOX1 (ARK1), which is orthologous to Arabidopsis SHOOT MERISTEMLESS (STM). ARK1 is expressed in the shoot apical meristem (SAM) and the vascular cambium, and is down-regulated in the terminally differentiated cells of leaves and secondary vascular tissues that are derived from these meristems. Transformation of Populus with either ARK1 or STM over-expression constructs results in similar morphological phenotypes characterized by inhibition of the differentiation of leaves, internode elongation, and secondary vascular cell types in stems. Microarray analysis showed that 41% of genes up-regulated in the stems of ARK1 over-expressing plants encode proteins involved in extracellular matrix synthesis or modification, including proteins involved in cell identity and signaling, cell adhesion, or cell differentiation. These gene expression differences are reflected in alterations of cell wall biochemistry and lignin composition in ARK1 over-expressing plants. Our results suggest that ARK1 has a complex mode of action that may include regulating cell fates through modification of the extracellular matrix. Our findings support the hypothesis that the SAM and vascular cambium are regulated by overlapping genetic programs.